2010
DOI: 10.1074/jbc.m110.116392
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific Prolongation of Kv7 (KCNQ) Potassium Channel Opening Mediated by New Molecular Determinants for Drug-Channel Interactions

Abstract: Kv7 channels, especially Kv7.2 (KCNQ2) and Kv7.3 (KCNQ3), are key determinants for membrane excitability in the brain. Some chemical modulators of KCNQ channels are in development for use as anti-epileptic drugs, such as retigabine (D-23129, N-(2-amino-4-(4-fluorobenzylamino)-phenyl)), which was recently approved for clinical use. In addition, several other compounds were also reported to potentiate activity of the Kv7 channels. It is therefore of interest to investigate compound-channel interactions, so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 43 publications
(56 reference statements)
3
63
0
Order By: Relevance
“…Similar to previous work, [4][5][6]14 we found that LAD coronary arteries from SHRs exhibited considerably less K V 7.4 protein compared with arteries from Concentration-dependent effect curve of K V 7 inhibitor XE-991 and linopirdine (C) in NT and spontaneously HT rats on arterial tone. Data are mean±SEM.…”
Section: K V 7 and Kcne Expression In Rat Coronary Arteriessupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to previous work, [4][5][6]14 we found that LAD coronary arteries from SHRs exhibited considerably less K V 7.4 protein compared with arteries from Concentration-dependent effect curve of K V 7 inhibitor XE-991 and linopirdine (C) in NT and spontaneously HT rats on arterial tone. Data are mean±SEM.…”
Section: K V 7 and Kcne Expression In Rat Coronary Arteriessupporting
confidence: 77%
“…Voltage-gated potassium channels (K V ) have been implicated in the control of the coronary circulation and reactive hyperemia, 1,2 but little is known about the specific molecular components. Kv channels encoded by KCNQ1-5 (K V 7.1-K V 7.5) are important regulators of the smooth muscle resting membrane potential and contractility in several different rodent and human arteries, [3][4][5][6][7][8][9][10][11] which are known to be compromised in animal models of primary and secondary hypertension. 3,6 These channels, in particular K V 7.4, are also functional end points in β-adrenoceptor-mediated relaxations.…”
mentioning
confidence: 99%
“…**Significant difference between all groups (P , 0.01 one-way ANOVA). Gao et al, 2010). Ztz240 activated homomeric Kv7.4 and Kv7.5 channels with similar potencies (Gao et al, 2010), whereas we found that ICA-069673 had no appreciable effect on homomeric Kv7.5 at concentrations up to 100 mM.…”
Section: Discussionmentioning
confidence: 46%
“…Gating modifiers of Kv7 channels include two groups of structurally unrelated compounds: N-pyridyl and pyrimidine benzamides (ICA-27243, ICA-069673, and ztz240) and N-phenylanthranilic acid derivatives (diclofenac, meclofenamic acid (2-[(2,6-dichloro-3-methylphenyl) amino]benzoic acid), and NH29 (2-[(2, 6-dichloro-4-nitrophenyl)amino]-N-(hydroxymethyl)-3,5-dinitrobenzamide) (Peretz et al, 2007;Wickenden et al, 2008;Padilla et al, 2009;Peretz et al, 2010;Gao et al, 2010;Amato et al, 2011;Li et al, 2013). ICA-069673 and ICA-27243 have similar structures, sharing the same two fluorines in a phenyl ring and an amide linker between aromatic rings, but ICA-27243 has a 6-chloro-pyridine ring, whereas ICA-069673 has a 2-chloro-5-aminopyrimidine ring (Amato et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Besides retigabine and ZnPy, there are several compounds capable of augmenting KCNQ channels, and several different key residues conferring the drug sensitivity have been identified (19). Indeed, some of these drugs, although different from ZnPy, also augment the KCNQ2 W236L mutant channels, e.g., ztz240 and ICA-27243 (20)(21)(22). Recent evidence suggests a direct drug-channel interaction with the voltage-sensing domain (VSD) (23).…”
Section: W236lmentioning
confidence: 99%